Timing of Early Salvage Therapy for Patients With Biochemical Relapse of Prostate Carcinoma - Argalácsová, Soňa; Vočka, Michal; Čapoun, Otakar; Lambert, Lukáš (Oncology reviews, 2023)
Between 25% and 33% of patients after radical prostatectomy experience a relapse of the disease. The risk of relapse increases in patients with risk factors up to 50%-80%. For a long time, adjuvant radiotherapy has been considered the standard of care. Four large prospective trials, that compared adjuvant and salvage radiotherapy in patients with biochemical relapse, showed the superiority of the adjuvant approach in biochemical and local relapse-free survival, but no consistent benefit in long-term endpoints (i.e., metastasis-free survival, overall survival, or carcinoma-specific survival) at the expense of increased urinary and bowel toxicity. Three large international studies comparing adjuvant and salvage radiotherapy paved the way toward early salvage radiotherapy. However, the optimal threshold of the PSA level (range of 0.2-0.5 ng/mL) for initiating early salvage radiotherapy remains unresolved and still poses a challenge in everyday clinical practice when balancing the need for early radiotherapy and the associated toxicity. Imprecise stratification of biochemical relaps patients according to the risk of clinical relapse drives efforts to find additional molecular biomarkers that would improve the timing of the salvage therapy.